The Language Contact Phenomenon between Panglima Laot and Coastal Society in the West Aceh Region - Kesha, Cut Nabilla; Sitompul, Siti Jahria; Ikhsan, Ikhsan; Aduwina, Aduwina; Rizki, Julia (Universitas Teuku Umar, 2025)
This study explores the phenomenon of language contact between Panglima Laot, fishers, and government representatives in West Aceh, Indonesia. The research aims to analyze how linguistic interaction occurs in the context of policy communication within coastal communities and to identify the sociolinguistic forms of interference, integration, code-switching, and code-mixing that emerge during such interactions. Using a qualitative descriptive method, data were collected through interviews and field observations involving government officials, Panglima Laot, and local fishers. The findings reveal that Panglima Laot functions as a linguistic and socio-cultural bridge, facilitating communication between the government and the fishing community. Language contact occurs due to differences in linguistic backgrounds Indonesian used by officials and Acehnese or the Jamu dialect used by fishers. The study shows that code-switching and code-mixing serve as effective strategies for ensuring mutual understanding, while interference and integration reflect linguistic adaptation and cultural assimilation. These linguistic practices not only improve policy comprehension but also strengthen social cohesion and trust between stakeholders. The research highlights the significance of local language and traditional leadership in enhancing communication effectiveness and ensuring the successful implementation of government policies in coastal regions.